The Pregnancy and Delivery with Cardiac Disease in Dr. Soetomo Hospital 2018 - Rahayu, Ana Puji; Gumilar, Khanisyah Erza (UNUSA Press, 2021)
Background: Cardiac disease is one of the non obstetric problems causing mortality both in pregnancy and labor due to the complications. Preventions for the complications have not been implemented, thus the number of patients which have cardiac disease with complications and perinatal outcome with low birth weight is still high. Objective : To identify maternal and neonatal outcome of pregnant women with cardiac disease in dr. Soetomo Surabaya hospital in 2018. Method: Descriptive retrospective study using medical records in dr. Soetomo Surabaya hospital 2018. Result: We found 1433 pregnancy cases with 51 (3,6 %) patients were having cardiac disease and included in this research. The most common maternal complication was pulmonary hypertension 16 cases. A dead case was found 1 case (1,9 %) with eissenmenger syndrome. We found the perinatal outcome of 30 babies (58.8%) born with a weight of 2500 gram and under. There are 7 patients with cardiac disease that have been corrected (13,7%). Among those 7 patients, 6 had a perinatal outcome with a birth weight of more than 2500 gram. Conclusion : Most pregnant patients with cardiac disease in dr. Soetomo Surabaya hospital 2018 are already having some complications with perinatal outcomes of low birth weight. Therefore, management of cardiac disease in pregnancy to prevent complications by means of preconception counseling, good antenatal care, and appropriate referrels are still needed to improve the quality of maternal and neonatal outcomes.